Model Aplikasi Human Resource Management Sistem (HRIS) Dengan Framework UniGui - Sufajar Butsianto; Candra Naya (Bulletin of Information Technology (BIT), 2023)
This research aims to build a Human Resource Information System of PT. XYZ will manage existing human resources, starting from the process of managing employee data, employee attendance, employee leave, employee permits, employee overtime and employee training history. This research uses a qualitative approach with an exploratory case study methodology by focusing research on the design of the Human Resources Information System (HRIS). The system development method used is waterfall. The analysis and design tools used are Unified Modelling Language (UML) using Usecase Diagrams and Class Diagrams. The programming language used is Delphi with the unuGUI framework and databases using SQL Server. This research successfully designed and built a Human Resource System (HRIS) Application and has been tested using Blackbox testing. The benefits of this application can make it easier for companies to manage employee data data, employee attendance, employee leave, employee permits, employee overtime and employee training history, and make it easier for companies to adapt to remote working and Work From Anyware (WFA) culture